Single‐ and multiple‐dose study to evaluate pharmacokinetics, safety and tolerability in healthy volunteers: A comparison of extended‐release oxycodone with sequestered naltrexone 40 mg twice daily to oxycontin 40 mg twice daily and extended‐release oxycodone with sequestered naltrexone 80 mg once daily. Issue 5 (22nd January 2015) - Gandelman, Kuan; Lamson, Michael; Bramson, Candace; Matschke, Kyle; Salageanu, Joanne; Malhotra, Bimal
Abstract ALO‐02 capsules (ALO‐02) contain pellets that consist of extended‐release oxycodone that surrounds sequestered naltrexone. The primary objective was to characterize the pharmacokinetics (PK) of oxycodone following single‐ and multiple‐dose oral administration of ALO‐02 40 mg BID in healthy volunteers. Secondary objectives were to characterize (1) the PK of oxycodone following single‐ and multiple‐dose administration of a comparator OxyContin (OXY‐ER) 40 mg BID as well as an alternate regimen of ALO‐02 80 mg QD, and (2) the safety and tolerability assessments. Healthy volunteers received three treatments on a background of oral naltrexone (50 mg). Noncompartmental PK parameters were calculated for oxycodone. All 12 subjects were male with a mean age (SD, range) of 44.6 years (7.6, 25–55). Single‐dose PK results for ALO‐02 indicate that median peak plasma oxycodone concentrations were reached by 12 hours compared to 4 hours for OXY‐ER. Compared to OXY‐ER, mean dose‐normalized, single‐dose Cmax values were approximately 27% and 23% lower for ALO‐02 40 mg BID and ALO‐02 80 mg QD treatments, respectively. Following multiple doses all treatments reached steady state by 3 days. At steady state, oxycodone peak‐to‐trough fluctuation was significantly lower for ALO‐02 BID versus OXY‐ER. Adverse events were consistent with opioid therapy. ALO‐02 40 mg BID treatment provided a PK profile appropriate for around‐the‐clock treatment of chronic pain.